Receptor-like kinase OsASLRK regulates methylglyoxal response and content in rice - LIN Fa-ming; Shen LI; Ke WANG; Hao-ran TIAN; Jun-feng GAO; Chang-qing DU (Journal of Integrative Agriculture, 2021)
Receptor-like kinases (RLKs) are essential for plant abiotic stress responses. Methylglyoxal (MG) is a cellular metabolite that is often considered to be a stress signal molecule. However, limited information is available about the relationship between RLKs and MG. Here, we addressed the function of a receptor-like kinase, OsASLRK, in the MG response and content in rice. A typical MG-responsive element (AAAAAAAA) exists in the promoter region of the OsASLRK gene. RTqPCR analysis indicated that the transcript level of OsASLRK was significantly increased by exogenous MG in a time- and dosage-dependent fashion. GUS staining also confirmed that the expression of OsASLRK in rice root was enhanced by exogenous MG treatment. Genetic analysis suggested that the Osaslrk mutant displays increased sensitivity to MG and it showed higher endogenous MG content under exogenous MG treatments, while OsASLRK-overexpressing rice plants showed the opposite phenotypes. Diaminobenzidine (DAB) staining, scavenging enzyme activities and GSH content assays indicate that OsASLRK regulates MG sensitivity and content via the elevation of antioxidative enzyme activities and alleviation of membrane damage. Therefore, our results provide new evidence illustrating the roles that receptor-like kinase OsASLRK plays in MG regulation in rice.